Vertical farming for higher profit and family nutrition - Behera, U K; Mohapatra, Priyadarshani P (Indian Horticulture, 2021)
Vertical farming is the practice of growing crops in vertically inclined surfaces. Instead of farming vegetables and other foods on a single level, such as in a field or a greenhouse, this method produces foods in vertically stacked layers commonly integrated into other structures like a skyscraper, shipping container or repurposed warehouse. Primary goal of vertical farming is producing more foods per square meter and to produce food and other items in doorstep in an urban culture to meet the need of various items of the family members. To accomplish this goal, crops are cultivated in stacked layers in a tower structure. The main advantage of utilizing vertical farming technologies is the increased crop yield that comes with a smaller unit area of land requirement. The increased ability to cultivate a larger variety of crops at once because crops do not share the same plots of land while growing is another sought-after advantage. Because of its limited land usage, vertical farming is less disruptive to the native plants and animals, leading to further conservation of the local flora and fauna. It offers a plan to handle future food demands. It allows crops to grow year-round and uses significantly less water. It can be used for organic vegetable production with less exposure to chemicals and diseases.